(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzed the importance of the Zarafshan River and the historical geography of the oasis in the creation of the anthropogenic landscape in the Bukhara oasis. These scientific evidences have been proven by the results of scientific research conducted at archaeological sites in the country. The topographical location of primitive community spaces found in the basin of the ancient valleys of the Lower Zarafshan oasis shows that the role of water bodies in the lifestyle of communities is incomparable. Based on this, we can say that the importance of 35 canals starting from the Zarafshan River in the settlement of mankind in the Bukhara oasis and the formation of the region has been proven. Therefore, in this article, the role and importance of irrigation networks in the formation of Bukhara oasis was studied.